Progress in screening strategies for neonatal developmental dysplasia of the hip - Han, Jiuhui; Li, Yu (Frontiers in Surgery, 2022)
Developmental dysplasia of the hip (DDH) is the most common congenital disease of the musculoskeletal system in newborns and encompasses a disease spectrum ranging from a stable hip with a mildly dysplastic acetabulum to complete hip dislocation. Systematic screening for infant DDH has been performed for several decades all over the world and has contributed greatly to the early detection, diagnosis and treatment of DDH. However, some cases of delayed diagnosis still occur among the screened population, or conversely, overdiagnosis or overtreatment occasionally occurs. Furthermore, screening strategies for DDH are still controversial. The aim of our study was to analyze the current literature on DDH screening, paying particular attention to DDH screening strategies and their effectiveness. We searched the DDH screening literature from 1958 to 2021 in MEDLINE and other databases using PubMed. In this study, we reviewed the history of DDH screening and the progress of screening strategies and discussed the controversies regarding clinical and ultrasound screening methods with particular emphasis on the current opinions. Given the existing scientific evidence and changes in newborn DDH screening practices, universal ultrasound screening seems to be the best option for preventing late-detected cases and can be recommended as a favorable prevention strategy.